Vital Components of Information Systems: Institutions and Human Resources - Rajagopalan, T. S.; Rajan, T. N. (Journal of Information and Knowledge, 1983)
Presents an evolution of the information systems and their contexts in the knowledge industry. Discusses the ramifications of the emergence of discipline, mission and problem-solving approaches to knowledge creation and the consequent development information resources in India.